Kajian Pemanfaatan IoT Berbasis LPWAN Untuk Jaringan Akuisisi Data ARG - Tri Istiana; R Yudha Mardyansyah; G.S Budhi Dharmawan (Elektron : Jurnal Ilmiah, 2020)
One of parameters for observing weather elements is the amount of rainfall. The rainfall observation system is using ARG. The existing condition uses cellular network-based IoT. In this study, researchers tried to provide an alternative communication system for ARG data acquisition networks using LPWAN-based IoT technology. Comparison of three LPWAN IoT technologies that can be applied to ARG communication systems, namely NB-IoT, Sigfox, and LoRaWAN. The three LPWAN technologies have followed the Republic of Indonesia Minister of Communication and Information Regulation No. 1 of 2019. These three technologies can be used for ARG data acquisition networks. LoRaWAN technology in rural areas reaches 20 km. LoRaWAN devices that meet frequency requirements have been sold freely on the internet with the 920 MHz frequency band. Of these three technologies, only LoRaWAN can be used to build private or internal communication networks. This is an added value for BMKG to build district or provincial scale LPWA WAN networks in regions that are constrained by the transmission of ARG data through cellular networks.